The Correspondence Theory of Mathematical Objects: on Automatism and Intersubjectivity - Prado, Belen (Resonancias. Revista de Filosofía, 2021)
This work promotes a philosophical reading of mathematics that responds to the political traumas of our time. The automated decisions driven by advanced information processing (AI) renews the prevailing tension of isomorphism or correspondentism between structural attributes of the mathematical sphere and those of the subjective sphere. Based on this tension, first, it is proposed to give a clear view on the difference between the methodological-instrumental and ontological-representational view of mathematics. Second, in order to give a new meaning to mathematical reality beyond an instrumental and formalist sense, Gaston Bachelard's view on mathematics allows to reflect on the relation within mathematics as a way of organizing experience. Therefore, it analyzes his study on mathematical determinism. With this, it aims to subvert the tension and classic political problem (automatism-intersubjectivity) driven in the digital-studies agenda.